2017
DOI: 10.1186/s40575-017-0046-4
|View full text |Cite
|
Sign up to set email alerts
|

Demography and disorders of German Shepherd Dogs under primary veterinary care in the UK

Abstract: BackgroundThe German Shepherd Dog (GSD) has been widely used for a variety of working roles. However, concerns for the health and welfare of the GSD have been widely aired and there is evidence that breed numbers are now in decline in the UK. Accurate demographic and disorder data could assist with breeding and clinical prioritisation. The VetCompassTM Programme collects clinical data on dogs under primary veterinary care in the UK. This study included all VetCompassTM dogs under veterinary care during 2013. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 76 publications
5
35
7
Order By: Relevance
“…Male Chihuahuas were significantly more likely to be neutered than female Chihuahuas (31.8% versus 22.0%). This contrasts to the findings of many other breedrelated studies that reported higher proportional neutering in females [13,27,34,35,43,44] although male French Bulldogs were also more likely to be neutered than females [28]. Both Chihuahuas and French Bulldogs are breeds with rapidly rising popularity and consequently youthful populations.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Male Chihuahuas were significantly more likely to be neutered than female Chihuahuas (31.8% versus 22.0%). This contrasts to the findings of many other breedrelated studies that reported higher proportional neutering in females [13,27,34,35,43,44] although male French Bulldogs were also more likely to be neutered than females [28]. Both Chihuahuas and French Bulldogs are breeds with rapidly rising popularity and consequently youthful populations.…”
Section: Discussioncontrasting
confidence: 91%
“…The current study identified a higher prevalence for aggression in males compared with females (4.9% versus 3.5%). A male predisposition to aggression is supported by a substantial body of evidence for several breeds [40][41][42][43][44][45]. A deeper understanding of this predisposition, including whether different interventions may be required for male or female dogs to either prevent the development of aggressive behavior, or treat it once established requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is widely reported that average longevity reduces as breed bodysize increases [ 42 , 50 55 ]. However, this 9.0 years longevity in Rottweilers compares poorly with the median longevity of 10.3 years reported for German Shepherd Dogs in the UK using a similar methodology and does suggest that the Rottweiler is a relatively short-lived breed [ 56 ].…”
Section: Discussionmentioning
confidence: 79%
“…VetCompass in the UK has been highly productive with the publication of peer-reviewed mortality studies on dogs [ 3 ] and cats [ 4 ]; longevity and prevalence reports on several breeds (e.g., Cavalier King Charles spaniels [ 50 ], pugs [ 51 ] and German Shepherd dogs [ 52 ]); multi-breed assessments of gastric dilation-volvulus [ 53 ], dystocia [ 54 ], diabetes mellitus [ 55 ], and audits of anti-microbial usage in companion animal practice [ 56 ]. The Australian consortium plans to apply the same methods to data on local dogs and publish matching reports so that comparison between breeds in the two countries can be made.…”
Section: Project Governancementioning
confidence: 99%